2015
DOI: 10.1063/1.4913208
|View full text |Cite
|
Sign up to set email alerts
|

Domain size engineering in 0.5%MnO2-(K0.5Na0.5)NbO3 lead free piezoelectric crystals

Abstract: The piezoelectric property of [001]-oriented 0.5%MnO2-(K0.5Na0.5)NbO3 (Mn-KNN) crystals was studied as a function of domain size, being poled with different electric fields at 205 C (above orthorhombic to tetragonal phase transition temperature To-t). The piezoelectric coefficients d33 and relative dielectric constants er were found to increase from 270 pC/N to 350 pC/N and 730 to 850 with the domain size decreasing from 9 to 2 lm, respectively. The thermal stability of piezoelectric property was investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…2,4 Significant efforts have been dedicated to addressing this issue; for example, attempts were made to lower the O-T phase transition temperature (T O-T ) to below room temperature and to synthesize highly textured KNN-based ceramics or single crystals. 2,7,[12][13][14][15][16] Unfortunately, the former failed to have good piezoelectricity (e.g., d 33 <300 pC/N) and the latter is too expensive for industrial applications. 7,12,13,15,16 Recently, composite designs of lead-free ceramics were proposed with both greater temperature stability and enhanced electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Significant efforts have been dedicated to addressing this issue; for example, attempts were made to lower the O-T phase transition temperature (T O-T ) to below room temperature and to synthesize highly textured KNN-based ceramics or single crystals. 2,7,[12][13][14][15][16] Unfortunately, the former failed to have good piezoelectricity (e.g., d 33 <300 pC/N) and the latter is too expensive for industrial applications. 7,12,13,15,16 Recently, composite designs of lead-free ceramics were proposed with both greater temperature stability and enhanced electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,[12][13][14][15][16] Unfortunately, the former failed to have good piezoelectricity (e.g., d 33 <300 pC/N) and the latter is too expensive for industrial applications. 7,12,13,15,16 Recently, composite designs of lead-free ceramics were proposed with both greater temperature stability and enhanced electrical properties. [17][18][19][20][21] For example, ferroelectric/relaxor composite ceramics consisting of a nonergodic relaxor (0.93BNT-0.07BT) and an ergodic relaxor (0.92BNT-0.06BT-0.02KNN) showed a low critical electric field required for inducing giant strain and a considerably low strain hysteresis, which was interpreted with a model based on two serially-connected capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MnO 2 addition could endow single crystals of KNN systems with a better piezoelectric response by modifying domain structure or lattice defects. [27][28][29] Besides, MnO 2 is deemed as one of the most intriguing additives in KNN-based ceramics because both "softening" or "hardening" characteristics of MnO 2 are simultaneously observed, which conduce to the increases in piezoelectric constant d 33 , relative permittivity e r , planar electromechanical coupling factor k p , and mechanical quality factor Q m , as well as the decrease in loss tangent tan d. [22][23][24][25][30][31][32] It has been found that a gentle decrease in T O-T and piezoelectric property enhancement could be achieved by the addition of AgSbO 3 . 33 As reported in previous work, 16,19 promising piezoelectric properties were achieved by the precise control of PPT point around room temperature in the AgSbO 3 -modified (Li, K, Na)(Nb,Ta)O 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this phenomenon could not be exactly surveyed using PLM owing to the misalignment between domain walls and light beam. 36 However, from the viewpoint of free energy, we can interpret this result by studying the temperature-dependent piezoelectric property, as will be discussed later. When the temperature was prior to T C (183 o C), a total optical extinction spread over the crystal, indicating the formation of the paraelectric phase, as shown in Fig.…”
Section: Domain Configurationmentioning
confidence: 99%
“…Previous reports suggest that the thickness of small domain size would increase the domain wall energy density. 36,40,41 In other words, according to free energy, the domain state will be unstable in the scope of phase transition, which immensely enhances the extrinsic contributions to the piezoelectric response, leading to the high piezoelectric coefficient around T R-T . From this point of view, the 33 * should be higher than that in T phase, which is consistent with the result shown in Fig.…”
Section: Thermal Stabilitymentioning
confidence: 99%